先化简,再计算:-2(3a-b)+(3a+5b)其中a=-2,b=3
1个回答
原式=-6a+2b+3a+5b=-3a+7b
当a=-2,b=3时
原式=-2*(-3)+7*3=27
相关问题
(5a^2-3b^2)-3(a^2-b^2)-(-b^2)先化简再求值其中A=5 B=-3
先化简,再求值:(√a+√b)²-(√a-√b)²,其中a=2+√3,b=2-√3
先化简,再求值:(3a+2b)(2a-3b)-(a-2b)(2a-b),其中a=-1.5,
先化简,再求值:4(a2-5a+b)-3(a2-6a-3b2),其中a=-3,b=-2.
(1)先化简,再求值:(a+b)²+(a-b)(a+b)-3a²,其中a=√3+2,b=√3-2
先化简再求值 (3a+2b)(3a-3b)-(a-2b)(2a-b),其中a=-1.5,b=1/4
先化简,再求值:(2a-3b)(3b+2a)-(2a-3b)²,其中:a=-2,b=-1
先化简,再求值:[(3a+2b)(3a-2b)-(a+2b)(5a-2b)]÷4a,其中a=2,b=-3
先化简,再求值:(a+b)(a-b)+(a+b)2-2a2,其中a=3,b=-[1/3].
先化简,再求值:(a+b)(a-b)+(a+b)2-2a2,其中a=3,b=-[1/3].